Sydney epilepsy incidence study to measure illness consequences: the SESIMIC observational epilepsy study protocol - Hackett, Maree L (BioMed Central, 2011)
BACKGROUND: Epilepsy affects an estimated 50 million people and accounts for approximately 1% of days lost to ill health globally, making it one of the most common, serious neurological disorders. While there are abundant global data on epilepsy incidence, prevalence and treatment, there is a paucity of Australian incidence data. There is also a general lack of information on the psychosocial impact and socioeconomic consequences of a new diagnosis of epilepsy on an individual, their family, household, and community which are often specific to the health and social system of each country. METHODS/DESIGN: The Sydney Epilepsy Incidence Study to Measure Illness Consequences (SEISMIC) is an Australian population-based epilepsy incidence and outcome study that will recruit every newly diagnosed case of epilepsy in the Sydney South West Area Health Service to an epilepsy register. Multiple and overlapping sources of notification will be used to identify all new cases of epilepsy over a 24 month period in the Eastern Zone of the Sydney South West Area Health Service (SSWAHS) and follow up will occur over 12 months. SEISMIC will use the International League Against Epilepsy (ILAE) definitions and classifications for epidemiologic studies of epilepsy. The study will examine outcomes including mood, quality of life, employment, education performance, driving status, marital and social problems, medication use, health care usage, costs and stigma. DISCUSSION: This study is designed to examine how clinical, psychological factors, socioeconomic circumstances, and healthcare delivery influence the experience of epilepsy for individuals and families allowing better targeting of specific services and informing policy makers and practitioners. In addition, the study will provide the basis for a longitudinal population-based cohort study and potentially inform qualitative sub-studies and randomised controlled trials of intervention strategies. The study has been registered on the Australia New Zealand Clinical Trial Registration database with ANZCTRN12609000059268.